Study on resistance mechanisms and molecular epidemiology of carbapenem-resistant Pseudomonas aeruginosa to ceftazidime/avibactam in a certain region of China - Qiao, Xiaohan; Zhang, He; Xu, Yao; Cao, Ting; Wang, Ruobing; Deng, Xinyu; Liang, Wei; Zheng, Lin (Frontiers in Cellular and Infection Microbiology, 2025)
Carbapenem-resistant Pseudomonas aeruginosa(CRPA) poses a serious threat in healthcare settings due to its multidrug resistance and high mortality. Although ceftazidime/avibactam (CZA) demonstrates potent activity against CRPA, resistance has emerged.ObjectiveThis study investigates the epidemiology and molecular mechanisms of CZA resistance in CRPA isolates from Ningbo, China.MethodsA total of 279 non-duplicate clinical CRPA isolates (2022–2024) were classified as CZA-resistant (CZA-R, n = 68) or CZA-susceptible (CZA-S, n = 211). Carbapenemase genes were detected by PCR, clonality via MLST, biofilm formation by crystal violet assay, and efflux pump expression (mexA, mexC, mexE, mexY) via qRT-PCR. WGS was performed on selected isolates.ResultsThe CZA resistance rate was 24.37%. Risk factors included recent trauma, prior antibiotic exposure, central venous catheterization, and drainage tube placement (all p < 0.05). The CZA-R group showed higher recurrence (13.2% vs. 4.3%, p = 0.029) and lower clinical improvement (67.6% vs. 77.3%, p = 0.029). blaNDM prevalence was higher in CZA-R (7.4% vs. 0.5%, p = 0.003), and ST1076 was the predominant clone (29.3%), with higher representation in CZA-R (40.0%). Horizontal gene transfer mediated blaNDM spread. CZA-R isolates exhibited enhanced biofilm formation (p < 0.001) and mexA upregulation (2.04-fold, p = 0.007).ConclusionOur findings indicate a high prevalence of CZA resistance among CRPA isolates in Ningbo, driven by multiple mechanisms including blaNDM carriage, enhanced biofilm formation, and overexpression of efflux pumps. The dissemination of the high-risk clone ST1076 underscores the need for strengthened infection control measures to curb its spread. These findings provide important insights for optimizing infection control and treatment strategies against CRPA infections in this region.